THE RELATIONSHIP BETWEEN SELF-EFFICACY AND QUALITY OF LIFE AMONG HYPERTENSIVE PATIENTS AT THE KEDUNGMUNDU COMMUNITY HEALTH CENTER - Rafael Krisananda Zefanya; Maria Agustina Ermi Tri Sulistiyowati; Maria Suryani (Jurnal Keperawatan Sriwijaya, 2026)
Aim: The quality of life patients with hypertension may decline due to uncontrolled blood pressure, poor therapy adherence, and inadequate self-care. Self-efficacy, defined as confidence in managing one’s illness, is a key factor that can enhance quality of life. Patients with high self-efficacy tend to adhere better to treatment and self-care, resulting in improved quality of life. This study aims to determine the relationship between self-efficacy and quality of life among hypertensive patients at Kedungmundu Public Health Center. Method: A cross-sectional study design was employed. A sample of 96 hypertensive patients was recruited using non-probability convenience sampling. Data collection instruments included a demographic questionnaire, the self-efficacy to manage hypertension questionnaire, and the WHOQOL-BREF Questionnaire. Data were analyzed using the spearman rank test. Result: The median value of self efficacy was 41.00. The mean score of overall quality of life was 66.99. The median score for the quality of life domains were 60.68 for the physical domain, 70.72 for the psychological domain, 66.62 for the social domain, and 68.75 for the environmental domain. Statistical analysis result showed a significant relationship between self-efficacy and quality of life (r=0.283, p=0.007). The correlations between self efficacy and quality of life domains were as follows: physical domain (r=0.097,  p=0.346), psychological domain (r=0.102, p=0.322), social domain (r=0.176, p=0.087), environmental domain (r=0.273, p=0.007). Conclusion: There is a weak positive relationship between self-efficacy and quality of life,and self efficacy was found to be relationship only with the environmental domain of quality of life. The higher the self efficacy, the better the quality of life.